Information and Communication Technologies (ICTs) in Farming and Its Determinants: A Reference of Dhankuta, Nepal (OCEM Journal of Management, Technology & Social Sciences, 2024)
Traditional extension fails to fulfil the different demands of rural farmers, who are often cut off from mainstream information sources. The results highlight the importance of information and communication technologies (ICTs) in connecting smallholder farmers to larger agricultural information systems. A survey study was conducted in Danuta, Eastern Nepal, to assess the usage of ICTs and their determinants in farming. A total of two hundred and twenty-four households were randomly selected, and descriptive and inferential statistics were used to analyse the data. The findings revealed a significant reliance on traditional ICTs, mobile phones, radios, and televisions, with adoption rates ranging from 79% to 90.18%. However, newer technology, internet services and smartphone apps, had lower adoption, indicating a slow integration into farming methods. Market and weather information were highlighted as the key reasons for using ICTs in farming. A logistic regression analysis identified major factors in using ICTs in farming. Younger household heads were more likely to adopt ICTs, indicating a generational split in technology acceptability. Male household heads were more likely to use ICTs than females. Borrowing loans for farming has emerged as a significant facilitator of ICT adoption.Interestingly, decreased ICT usage was associated with higher academic status, highlighting the necessity for focused efforts to bridge this disparity. Overall, the study implies the role of ICTs in improving agricultural productivity and livelihoods in Nepal. Policymakers and stakeholders can use ICTs to empower farmers, improve information distribution, and promote sustainable agriculture by removing access barriers and fostering the digital literacy.